Functional Characterization of the Osteoarthritis Genetic Risk Residing at ALDH1A2 Identifies rs12915901 as a Key Target Variant. Issue 10 (23rd August 2018) - Shepherd, Colin; Zhu, Dongxing; Skelton, Andrew J.; Combe, Jennifer; Threadgold, Harrison; Zhu, Linyi; Vincent, Tonia L.; Stuart, Paul; Reynard, Louise N.; Loughlin, John
Abstract : Objective: To identify the functional single‐nucleotide polymorphisms (SNPs) and mechanisms conferring increased risk of hand osteoarthritis (OA) at the ALDH1A2 locus, which is a retinoic acid regulatory gene. Methods: Tissue samples from 247 patients with knee, hip, or hand OA who had undergone joint surgery were included. RNA‐sequencing analysis was used to investigate differential expression of ALDH1A2 and other retinoic acid signaling pathway genes in cartilage. Expression of ALDH1A2 in joint tissues obtained from multiple sites was quantified using quantitative reverse transcription–polymerase chain reaction. Allelic expression imbalance (AEI) was measured by pyrosequencing. The consequences of ALDH1A2 depletion by RNA interference were assessed in primary human chondrocytes. In silico and in vitro analyses were used to pinpoint which, among 62 highly correlated SNPs, could account for the association at the locus. Results: ALDH1A2 expression was observed across multiple joint tissue samples, including osteochondral tissue from the hand. The expression of ALDH1A2 and of several retinoic acid signaling genes was different in diseased cartilage compared to non‐diseased cartilage, with ALDH1A2 showing lower levels in OA cartilage. Experimental depletion of ALDH1A2 resulted in changes in the expression levels of a number of chondrogenic markers, including SOX9 . In addition, reduced expression of the OA risk–conferring allele was witnessed in a number of joint tissues, with the strongest effect in cartilage. The intronic SNP rs12915901 recapitulated the AEI observed in patient tissues, while the Ets transcription factors were identified as potential mediators of this effect. Conclusion: The ALDH1A2 locus seems to increase the risk of hand OA through decreased expression of ALDH1A2 in joint tissues, with the effect dependent on rs12915901. These findings indicate a mechanism that may now be targeted to modulate OA risk.